The Girl With The Dragon Tattoo - Larsson,Stieg (Alfred A. Knopf, 2010)
Title from container. Maps and illustrations on lining papers. Originally published as a box set. "Also includes On Stieg Larsson, a collection of previously unpublished essays about, and correspondence with, the author"--Case.